Serum NGAL to Clinically Distinguish Cholangiocarcinoma from Benign Biliary Tract Diseases - Kawin Leelawat; Siriluck Narong; Jerasak Wannaprasert; Surang Leelawat (International Journal of Hepatology)
Aim. To determine whether the serum level of NGAL can discriminate cholangiocarcinoma from benign biliary tract disease in patients. Methods. This study was performed according to a prospective-specimen-collection, retrospective-blinded-evaluation (PRoBE) design. A total of 50 cholangiocarcinoma and 50 benign biliary tract disease cases were randomly selected from a cohort of consecutive cases of biliary tract diseases. Their sera were measured for the levels of NGAL and the widely used serum cholangiocarcinoma marker, carbohydrate antigen 19-9 (CA19-9). Results. The serum CA19-9 and NGAL levels were significantly elevated in cholangiocarcinoma patients (CA19-9: 𝑃<.001, NGAL: 𝑃<.001). The area under the curve (AUC) of a receiver operating characteristic (ROC) curve analysis for the diagnosis of cholangiocarcinoma of CA19-9 and NGAL was 0.81 and 0.79, respectively. Conclusion. The diagnostic accuracy of serum NGAL and CA19-9 makes them good candidates for use as biomarkers to discriminate cholangiocarcinoma patients from benign biliary tract disease patients.